Enhanced narrow-band green-emission and thermal stability via the introduction of Mg2+ in ZnB2O4:Mn2+ phosphor. Issue 39 (17th September 2019) - Dong, Quan; Cui, Jun; Tian, Yabin; Jia, Junjie; Yang, Fengli; Du, Fu; Peng, Jiaqing; Ye, Xinyu; Yang, Shaohua
Abstract : The introduction of Mg 2+ in ZnB2 O4 :Mn 2+ may reduce the impurity phase, and increase the emission intensity and thermal stability by 100% and 9%, respectively. The mechanism is considered to be the ion-size compensation effect of Mg 2+ to Mn 2+ . Abstract : A narrow-band green-emitting phosphor ZnB2 O4 :Mn 2+, Mg 2+ was prepared by solid-state reactions. X-ray diffraction (XRD) and the Rietveld structural refinements were performed. The results show that the introduction of Mg 2+ may suppress the formation of an impurity phase. The micro-structure, photoluminescence (PL) and reflectance spectra, PL decay curves as well as thermal quenching behavior were investigated. The phosphors exhibit a broad absorption band from 200 to 510 nm, while the emission spectra show a narrow band centered at 538 nm with a full-width at half-maximum (FWHM) of about 34 nm. Furthermore, after the introduction of Mg 2+, the luminescence intensity of phosphor ZnB2 O4 :0.07Mn 2+, 0.10Mg 2+ is significantly enhanced by about 2 times, and it presents a relatively low thermal quenching behavior. The corresponding mechanisms for performance improvement were investigated in detail and the ion-size compensation effect of Mg 2+ to Mn 2+ is proposed. Additionally, the high activation energy (0.202 eV) and ultra-high color purity (97%) were calculated. These results imply that the ZnB2 O4 :Mn 2+, Mg 2+ phosphor has broad application prospects in the field of advanced backlight display. Moreover, the introduction of Mg 2+ may be useful as an effective strategy to enhance the luminescence properties and thermal stability of Mn 2+ or even other element-doped phosphors.